The Mediating Role of Online Customer Reviews in the Influence of Content Marketing on Purchase Decisions - Tri Lestari, Febrianti; Nurhasan, Rohimat; Wufron (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aims to analyze the mediating role of reviews uploaded by online consumers and their impact on purchase decisions on TikTok, particularly those influenced by content marketing. The research background indicates a rapid increase in TikTok usage for business activities, with Indonesia being the largest TikTok user country in July 2024. Although Content Marketing and Online Customer Review have been acknowledged to influence Purchase Decision, many previous researches has a gap in understanding mediation impact of Online Consumer Review in TikTok App specifically. Some studies also suggest that Content Marketing does not always significantly impact Purchase Decision on this platform. To collect the required primary data, this study uses a questionnaire that was addressed to 400 TikTok users in Indonesia, making this study classified into quantitative approach research-based. In this research, the data analyze technique has been uses the PLS-SEM through Smart PLS software. The review uploaded by online consumer has a strong-positive relationship to affect other consumers’ purchasing decision, this statement becomes the preliminary result then. Online Customer Review also has a very strong and positive relationship with the Purchase Decision. However, the direct relationship between Content Marketing and Purchase Decision is relatively weak. Initial findings indicate that Content Marketing has a very strong positive relationship with Online Customer Review (path coefficient of 0.920). Online Customer Review also has a very strong and positive relationship with Purchase Decision (path coefficient of 0.810). However, the direct relationship between Content Marketing and Purchase Decision is relatively weak (path coefficient of 0.146). This suggests that Online Customer Review plays a crucial role in mediating the influence of Content Marketing on Purchase Decision in TikTok. This study is expected to fill the literature gap by developing a mediation model that considers the specific characteristics of TikTok. This research is expected to fill the literature gap by developing a mediation model that considers the specific characteristics of TikTok.